An Interval Arithmetic Approach in solving Interval-Valued Trapezoidal Neutrosophic Fuzzy Multi-Objective Multi-Item Solid Transportation Problem - Sinika, S.; Ramesh, G. (Yugoslav Journal of Operations Research, 2025)
Unpredictability and uncertainty occur worldwide in various aspects of real life. We cannot predict some specific outcomes or events precisely due to multiple factors, randomness, complexity and limited information. These situations can be handled efficiently in a systematic way by using neutrosophic sets. In real-world applications, transportation is essential in all sorts of movement of goods, services and people to meet various needs and demands efficiently. This study concentrated on the multiple objectives, multiple choice transportation problem in interval-valued trapezoidal neutrosophic contexts. The conversion procedure employs a de-neutrosophication process that relies on interval numbers rather than crisp numbers. By using an interval-valued trapezoidal neutrosophic fuzzy programming method based on interval number, the identified uncertain transportation problem is then solved. Additionally, an illustrative instance is presented to showcase the successful implementation of the proposed methodology.